Fuzzy logic approach for evaluating energy losses at the Kasangulu electrical substation - Patrick, Bokungu Efoto; Rostin, Mabela Makengo; Nathanael, Kasoro Mulenda; Dupar, Kampempe Kyemba Justin; Jacques, Nyembo Biyule; Louis, Efoto Eale (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2027)
The reliability of an electrical network depends mainly on service continuity and the quality of data from distribution stations. This data contains quantifiable inaccuracies and measurement errors, which complicates the detection of anomalies using traditional methods. This study proposes the application of fuzzy logic to analyze the energy balance for the years 2019-2023 for the Kasangulu electrical substation. The methodology is based on the fuzzification of electrical quantities (energy delivered to the grid, energy sold, efficiency) and the development of a fuzzy inference system in accordance with the Mamdani method. The results obtained show that fuzzy logic provides a more effective solution to measurement inaccuracy and uncertainty, offering more accurate anomaly detection than conventional deterministic techniques. This approach is an effective decision-making tool for the monitoring and predictive maintenance of the electricity grid in general and Kasangulu in particular.